TINJAUAN ATAS PROSEDUR PENERIMAAN DAN PENGELUARAN KAS PADA LRT CITY CIBUBUR - Kania Iswara (2023)
Management Information related to financial conditions, performance and changes in financial conditions is needed to be able to assess a company's ability to generate cash, as well as timing and certainty of results. This study concludes how to review the procedures for receiving and disbursing cash at PT Adhi Commuter Properti LRT City Cibubur Regional Office, namely by collecting data and information obtained using Field Research Methods (Field Research), certain information and data collected during the data collection stage are subject to qualitative descriptive analysis method. The results showed that PT Adhi Commuter Properti's cash receipts from the LRT City Cibubur Area Office were documented as being received from two sources: Consumer Cash In and PT Adhi Commuter Properti's head office funding. Then show that cash disbursements are used to pay for regional office operational activities, bills and other costs. In short, PT Adhi Commuter Properti Regional Office LRT City Cibubur in the procedure for receiving and disbursing cash uses a cash basis and uses a supporting account, namely a cross-section account for cash receipts.